Componentes anatómicos y coeficientes alométricos en cerdos machos castrados desde el nacimiento - Casas, Gloria A.; Afanador, Germán; Rodríguez, Daniel (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This paper describes the changes in anatomic components such as carcass, viscera and organs in commercial genotype barrows from birth to 273 days old. The relationships between them were quantified by using allometric equations. To analyze the changes in anatomic components, 39 terminal cross barrows (four per age) were slaughtered. The barrows were 1, 21, 63, 99, 126, 154, 175, 210, 239 and 273 days old. Descriptive statistics were used and six allometric equations were evaluated. Empty body weight, carcass weight, total viscera mass and total red and white viscera mass showed a quadratic linear trend in relation to live weight. Carcass weight trend was linear (p < 0.0001) with regard to empty body weight. Evaluated organs increased their weight in a linear, quadratic and cubic way except for the spleen, whose trend was linear (P < 0.001). The same ratios (linear-quadratic) were observed in red, white and total viscera weight (p < 0.01). The equations that best described the relationship between body weight and the different body components and organs were the increased allometric and the linearized allometric equations. The intercept values obtained for the evaluated equations were different from the ones reported in the literature, probably due to the high selection pressure imposed on swine genotypes used for pork production. This selection pressure may imply physiological and anatomical changes.